Comparing L- and C-band synthetic aperture radar estimates of sea ice motion over different ice regimes - Howell, Stephen E.L.; Komarov, Alexander S.; Montpetit, Benoit; Dabboor, Mohammed; Brady, Michael; Scharien, Randall K.; Mahmud, Mallik S.; Nandan, Vishnu; Geldsetzer, Torsten; Yackel, John J. (Remote Sensing of Environment, 2018)
Estimating sea ice motion from synthetic aperture radar (SAR) imagery at C-band is the most reliable approach because of its high spatial resolution and ever increasing temporal resolution given the multiple current and upcoming SAR platforms. However, there is still uncertainty in SAR derived sea ice motion depending on the ice type and its thermodynamic state. There have been suggestions (mostly theoretical) that use of L-band SAR and its inherent longer wavelength (15–30 cm) and subsequent increased penetration capability could be beneficial for estimating sea ice motion, especially during the melt season. Here, we estimate and analyze sea ice motion for 9 pairs of C- and L-band SAR imagery from RADARSAT-2, PALSAR-1 and PALSAR-2 located in the Canadian Arctic over a variety of sea ice types at different thermodynamic states. Results show that the increased signal penetration of L-band SAR into multi-year ice (MYI) during the melt season facilitates the detection of more motion vectors with stronger cross-correlation coefficients compared to C-band SAR. Over newly formed ice and dry first-year ice, the reduced sensitivity to surface scattering and richer texture from L-band SAR imagery facilitates the detection of more motion vectors with stronger cross-correlation coefficients compared to C-band SAR. Over dry MYI, L-band provided stronger cross-correlation coefficients but C-band detected more motion vectors with a more representative spatial distribution. With Arctic sea ice continuing shift from a multi-year to first-year dominated icescape, coupled with an increasing melt season length, L-band SAR's ability to provide improved sea ice motion estimates during both the melt and freeze-up time periods could prove even more useful in the coming decades. PALSAR-2 images were provided by Japan Aerospace Exploration Agency (JAXA) under the 4th Research Announcement program (PI NO. 1202, S. Howell) and through a joint sharing agreement between Canadian Space Agency (CSA) and JAXA. PALSAR-1 images were provided ...